Anthropology Between Positivism and Constructivism or A Short Discourse on the Subject of One Sentence by Iva Heroldová - Jakoubek, Marek (Dějiny – teorie – kritika, 2012)
Th is article deals with the issue of the origin of the founders of community of St. Helena. In the fi rst part of the text, the author presents Nešpor’s hypothesis regarding the founders of this community, which identifies them as East-Bohemian tolerance sectarians. Th e second part of the study deals with a discrepancy between Nešpor’s hypothesis on the origin of this group and the group member’s conviction that they are descendants of exiles who left after the Battle at the While Mountain, while taking into account Nešpor’s conviction that these beliefs are erroneous. Based on a social anthropological perspective, the author argues that ‘if people believe that something is true, then it is true’ and in this sense, the members of the community are indeed descendants of the post-1620 exiles. On a general level, this dispute is treated as a difference of position between a positivist stance, shared by (Czech) ethnology and historiography, and the perspective of social constructivism, advocated in the given context by the nascent Czech social anthropology.